2012 19th IEEE International Conference on Image Processing 2012
DOI: 10.1109/icip.2012.6466795
|View full text |Cite
|
Sign up to set email alerts
|

From optical flow to dense long term correspondences

Abstract: Dense point matching and tracking in image sequences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…More recently, Crivelli et al [6] proposed an automatic method for mapping textures between images. They use optical flow as a basic algorithm to find trajectories with space-time continuity over the frames of video.…”
Section: B Editing Textures In Video Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Crivelli et al [6] proposed an automatic method for mapping textures between images. They use optical flow as a basic algorithm to find trajectories with space-time continuity over the frames of video.…”
Section: B Editing Textures In Video Sequencesmentioning
confidence: 99%
“…Because our algorithm only merges regions that have a smooth correspondence field together, after the algorithm is finished each region covered by a different B-Spline surface can be considered a different shared object. To test our algorithm against other methods, we performed a numerical comparison of our results with those of the Co-recognition work of Cho et al [9] and NRDC [1], shown in Table II [6], initial correspondences from NRDC [1], and the result of our Trivariate-Spline approximation. Errors in Crivelli et al's result are large, while the trajectory from NRDC is perhaps more accurate but very noisy (high variance).…”
Section: A Unsupervised Recognition and Segmentation Of Multiple Commentioning
confidence: 99%
“…It links each pixel x a of I a to a corresponding position in I b . Elementary optical flow fields can be computed between consecutive frames or with different frame steps [11,12], i.e. with larger inter-frame distances.…”
Section: Combinatorial Multi-step Integrationmentioning
confidence: 99%
“…Following a similar approach to that presented in [10], one can select for each pixel the optimal motion vector among a set of candidate motion fields based on intrinsic motion field quality and spatial regularization. A more sophisticated processing, described in [11,12], consists in sequentially merging a set of concatenated multi-step motion fields at intermediate frames up to the target frame. However, in either case, the optimal motion vector selection strongly depends on the same optical flow assumptions that frequently fail between distant frames.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative concept of multi-step flow (Crivelli et al, 2012b;Crivelli et al, 2012a) focuses on how to construct dense fields of correspondences over extended time periods using multi-step optical flows (optical flows computed between consecutive frames or with larger inter-frame distances). Multi-step flow sequentially merges a set of displacement fields at each intermediate frame, up to the target frame.…”
Section: Introductionmentioning
confidence: 99%